TATA CARA PENERBITAN FAKTUR PAJAK PENGGANTI DAN PEMBATALAN FAKTUR PAJAK (STUDI PADA FIRMA HLP CONSULTANT BANJARMASIN) - Nathania, Gracella; Sustinah Limarjani; Fatimah (Universitas Lambung Mangkurat, 2022)
The aim of this research is to analyze the effectiveness and contribution of the swallow's nest tax to local taxes in Tanah Bumbu district in 2019-2022. The method used in this research is quantitative descriptive. Data collection was carried out through interviews, documentation and observation. The research results show that tax efficiency in Tanah Bumbu Regency from 2019-2022 is quite good, but still not effective. This is due to ignorance of taxpayers, the influence of the price of swallow's nests on the market, tax avoidance and delays, as well as inadequate business permits and databases